2016
DOI: 10.1007/s13318-016-0354-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics After Single Ascending Dose, Food Effect, and Safety of Sacubitril/Valsartan (LCZ696), an Angiotensin Receptor and Neprilysin Inhibitor, in Healthy Japanese Subjects

Abstract: Single oral doses of up to 600 mg of LCZ696 were safe and generally well tolerated in healthy Japanese male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Valsartan is a strongly pH-dependent solubility drug, of which the absorption window is stomach and upper part of small intestine. Thus, absorption rate of valsartan could be decreased when it is taken with food in advance, as well as the exposure of valsartan is reduced 39 . For insights of effects to bioavailability of drugs by food, data sets for oral valsartan administered either fasted or fed were used for pharmacokinetic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Valsartan is a strongly pH-dependent solubility drug, of which the absorption window is stomach and upper part of small intestine. Thus, absorption rate of valsartan could be decreased when it is taken with food in advance, as well as the exposure of valsartan is reduced 39 . For insights of effects to bioavailability of drugs by food, data sets for oral valsartan administered either fasted or fed were used for pharmacokinetic modeling.…”
Section: Discussionmentioning
confidence: 99%
“…In one constituent study, the pharmacokinetics of Entresto following single ascending doses were only measured in healthy males (40 males enrolled). 61 In another constituent study, 29 males and 25 females were included, however sex-dependent analysis was conducted by pooling both young (18-45 years old) and elderly (≥65 years old) volunteers together, which could be confounded by menopause status (pre-, peri-& post-). 62 Sex-independent data within the same study demonstrated that Entresto clearance was significantly reduced with age.…”
Section: Sex Differences In Heart Failure Etiologiesmentioning
confidence: 99%
“…The effect of food on the pharmacokinetics of all the analytes (Table 3) was evaluated in healthy subjects following administrations of sacubitril/valsartan 400 mg with a low-fat meal (500-600 kcal) and a high-fat meal (800-1000 kcal) [24] and 200 mg of sacubitril/valsartan with a Japanese meal (*500 kcal, 14% fat) [30]. Administration of sacubitril/valsartan with food resulted in a decreased rate of absorption of sacubitril, as indicated by a delayed T max (by 1-2 h) and a decreased C max (by 48-72%).…”
Section: Effect Of Foodmentioning
confidence: 99%
“…Therefore, sacubitril/valsartan can be administered without regard to meals. Single-dose pharmacokinetics: data of sacubitril/valsartan 200 mg were pooled from five studies in healthy subjects [21,30,45,100; data on file for furosemide study (CLCZ696B2126) study]…”
Section: Effect Of Foodmentioning
confidence: 99%
See 1 more Smart Citation